Serum zinc deficiency is a potential risk factor for the occurrence of levodopa-induced dyskinesia in drug-naïve Parkinson’s disease - Kim, Joung Eun; Lee, Hyo Sang; Jang, Wooyoung (Frontiers in Aging Neuroscience, 2023)
Background Since environmental factors, especially heavy metals, were highlighted in the pathogenesis of Parkinson’s disease (PD), there are many epidemiologic studies regarding heavy metals and PD risk. However, longitudinal studies regarding the impacts of heavy metals on motor and nonmotor symptoms of PD are scarce. Methods In the current study, we compared the serum levels of five heavy metals, such as zinc(Zn), copper(Cu), lead(Pb), mercury(Hg), and manganese(Mn), in 111 previously drug-naïve PD patients (n = 111) retrospectively. Among these 111 patients, 65 were PD patients without levodopa-induced dyskinesia (LID), while the other 46 had LID. We assembled clinical characteristics of PD and performed correlation analysis with heavy metal levels. At baseline, all subjects were examined with 18F-N-(3-fluoropropyl)-2β-carboxymethoxy-3β-(4-iodophenyl) nortropane positron emission tomography/computed tomography (FP-CIT PET/CT). We used Cox proportional hazards regression analysis for determining factors relevant to the time to LID development in PD subjects. Results Zn deficiency was significantly higher in the PD with LID group than in the PD without LID group (79.58 ± 12.28 versus 88.16 ± 15.15 μg/L). Lower serum Zn levels were significantly correlated with age of onset, levodopa equivalent daily dose (LEDD) at 3 months, and Korean version of the Mini-Mental State Examination (K-MMSE) scores (r = 0.16, p < 0.05, r = − 0.20, p < 0.01, r = 0.28, p < 0.01). Additionally, Zn deficiency was associated with a reduced time to LID development in the adjusted model (HR 0.978, 95% CI 0.956–0.999). Conclusion This study suggests that serum Zn deficiency might be a risk factor for LID in drug-naïve PD patients.